Señalización horizontal y vertical de una carretera. caso práctico: vía perimetral entre los km. 20 y 30, Guayaquil-Ecuador - Miranda Villena, Héctor (2010)
Based on the Traffic Signs and Markings manual by the Colombian Bureau of Transportation, the one made by the INEN (Ecuadorian Institute of Normalization) and the MUTCD (Manual on Uniform Traffic Control Devices) also based on the traffic accidents statistics on year 2009 published by the “Comisión de Tránsito del Guayas” (CTG). The markings and signs on the “Vía Perimetral” street were evaluated between km 20 and 30 on 3 specific spots where the most traffic accidents have occurred. From the latter evaluation a design on traffic markings and signs was made with its proper economic proposal, with the objective of solving traffic problems on these hot spots, comprehend the theory and criteria involving the placing of traffic markings and signs and understand the justifications for the installation of a traffic light.